The Creation of Wing Chun : A Social History of the Southern Chinese Martial Arts - Judkins, Benjamin N., 1975- (Book collections on Project MUSE., 2015)
Looks at southern Chinese martial arts traditions and how they have become important to local identity and narratives of resistance.